An Analysis Magical Realism of Supernatural Phenomena As Seen in Lewiis Carroll’s Alice in Adventures Wonderland - Helmita, Helmita; Salsabila, Melinia (Fakultas Sastra Universitas Ekasakti, 2024)
The title of this research is